Intra-Familial Phenotypic Variability in Lipoid Proteinosis: A Case Series of Three Siblings. - Murtaza, Muhammad; Zafar, Insharah; Mubashar, Bareea; Samadi, Abedin; Raza, Ahmed Asad (Clinical Medicine Insights: Case Reports, 2026)
Lipoid proteinosis (LP), or Urbach-Wiethe disease, is an ultra-rare autosomal-recessive disorder caused by loss-of-function variants in the ECM1 gene. It is characterized by the progressive deposition of hyaline-like material in the skin, mucosae, and central nervous system. This series describes three siblings (aged 16, 24, and 25) from Gujranwala, Pakistan, born to non-consanguineous parents. All patients presented with infant-onset hoarseness of voice and recurrent vesiculobullous eruptions that evolved into waxy papules and hyperkeratotic plaques. Physical examination revealed the pathognomonic "beaded" eyelid papules (moniliform blepharosis), pock-like facial scarring, and a thickened lingual frenulum restricting tongue protrusion. Despite shared genetics, intrafamilial variability was observed, with the male sibling exhibiting a more severe "leonine-like" facies. Neuropsychiatric symptoms, including aggression and insomnia, were noted across the series. Due to resource constraints, the diagnosis was established clinically. Management focused on symptomatic control using oral acitretin (0.5 mg/kg/day), antihistamines, and intensive topical emollients. At 12-week follow-up, patients showed significant reduction in pruritus and stabilization of skin lesions, though hoarseness and established scarring remained unchanged. This series underscores the importance of recognizing cardinal clinical triads—moniliform blepharosis, mucosal tethering, and early hoarseness—to diagnose LP in resource-limited settings where genetic or histological confirmation is unavailable.